Efforts to Increase Student Interest in Science by Maximizing Laboratory Facilities at SMA Negeri 3 Unggulan Kayuagung - Sinulingga, Sehat; Fitria, Happy; Wahidy, Achmad (Journal of Social Work and Science Education, 2023)
This study aims to describe efforts to increase students’ interest in science by maximizing laboratory facilities at SMA Negeri 3 Unggulan Kayuagung. Data collection tools using interviews, documentation, observation, and literature review. Data analysis used descriptive qualitative analysis with research stages referring to Miles and Huberman’s theory, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the study stated that efforts to increase the interest of students of SMAN 3 Unggulan Kayuagung in the field of science facilities by maximizing laboratory infrastructure were carried out by 1) planning laboratory facilities to increase students’ interest in SMAN 3 Unggulan Kayuagung in the Field of Science, 2) observing the laboratory facilities and infrastructure of SMAN 3 Unggulan Kayuagung; 3) laboratory design for SMAN 3 Unggulan Kayuagung; 4) equipment selection for SMAN 3 Unggulan Kayuagung; 5) training for teachers and students of SMAN 3 Unggulan Kayuagung; 6) implementation of laboratory regulations for Unggulan Kayuagung SMAN 3, implementation, and 7) laboratory evaluation for SMAN 3 Unggulan Kayuagung.